Finite-Element Analysis of Three-Dimensional Axisymmetrical Invisibility Cloaks and Other Metamaterial Devices (Communications in Computational Physics, 2010)
Accurate simulations of metamaterial devices are very important in the analysisof their electromagnetic properties. However, it is very difficult to make full-wavesimulations of three-dimensional (3D) metamaterial devices due to the huge memoryrequirements and long computing time. In this paper, we present an efficient finite-elementmethod (FEM) to analyze 3D axisymmetric electromagnetic devices designedby the transformation-optics approach, such as invisibility cloaks and concentrators.In the proposed method, we use the edge-based vector basis functions to expand thetransverse field components, and the node-based scalar basis functions to expand theangular component. The FEM mesh is truncated with a cylindrical perfectly matchedlayer. We have applied the method to investigate the scattering from spherical and ellipsoidalinvisibility cloaks and circularly cylindrical concentrators, in which the permittivityand permeability are both inhomogeneous and anisotropic. Numerical resultsare presented to show the validity and efficiency of the method.